Advances in biologic and small molecule therapies for hidradenitis suppurativa. (24th May 2022) - Chen, Stella X.; Greif, Charlotte; Gibson, Ruby S.; Porter, Martina L.; Kimball, Alexa B.
ABSTRACT: Introduction: Hidradenitis suppurativa (HS) is a chronic, debilitating inflammatory skin disorder characterized by painful nodules, abscesses, fistulae, and scarring with a predilection for flexural regions. Several biologics and small molecule inhibitors are being evaluated in clinical trials for treatment. Areas covered: The authors discuss the data available from clinical trials and smaller, high-quality studies for existing and emerging biologic and small molecule inhibitor therapies for treatment of HS. Biologics discussed include TNFα, IL-17, IL-23, IL-12/23, and IL-1 inhibitors. Small molecule inhibitors discussed include PDE4, JAK, TYK, IFX-1, and complement cascade inhibitors. Pharmacokinetics and pharmacodynamics for these drugs are also described. Expert opinion: Trial data and our own experience have shown that about half of HS patients experience improvement with adalimumab. However, there is a significant need for pharmacotherapies with higher efficacy goals as in those used for psoriasis. Many biologics and small molecule inhibitors are being tested in clinical trials. The landscape of upcoming therapies for hidradenitis suppurativa appears promising.